2020
DOI: 10.1002/pen.25340
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hybrid Cellulose/Bentonite Fillers on Structure, Ambient, and Low Temperature Tensile Properties of Thermoplastic Starch Composites

Abstract: Thermoplastic starch (TPS) composites incorporating bentonite/cellulose (Bent/Cellulose) hybrid fillers in different ratios were prepared by film casting. Ultra‐sonication was done to promote good dispersion of filler in the host TPS and enhance the filler‐matrix interactions. Ultra‐sonicated fillers resulted in superior improvement in the tensile properties when the samples preconditioned at both ambient and 2°C. Upon preconditioning at 2°C, the TPS composite containing the ultra‐sonicated hybrid bent/cellulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 47 publications
(79 reference statements)
1
30
0
Order By: Relevance
“…Figure 7 indicates the FTIR spectra of the TPS film, TPS-5wt%DOL (P) and TPS-5wt%DOL(U) biocomposite films. It can be observed that the FTIR signal of the TPS film indicates a strong spectral band in the range of 600 to 1500 cm −1 , which confirms the fingerprint of the starch material [ 5 ]. TPS film displays the characteristics FTIR absorptions at 3265 and 2925 cm −1 , which correspond to the O-H and C-H stretching, respectively.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Figure 7 indicates the FTIR spectra of the TPS film, TPS-5wt%DOL (P) and TPS-5wt%DOL(U) biocomposite films. It can be observed that the FTIR signal of the TPS film indicates a strong spectral band in the range of 600 to 1500 cm −1 , which confirms the fingerprint of the starch material [ 5 ]. TPS film displays the characteristics FTIR absorptions at 3265 and 2925 cm −1 , which correspond to the O-H and C-H stretching, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…The reduction in particle size of dolomite has increased its surface area. As a result, signals from X-ray diffraction that went through the crystalline lattices of dolomite particles became stronger [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[2,3] Biopolymers like cellulose, chitin and starch have been studied and researched for packaging applications to substitute for synthetic plastics. [1][2][3] Composite materials based on biopolymers are gaining more attraction due to the mechanical performance of these materials which is almost always greater than their neat biopolymer counterparts. Lignocellulosic-based fibers from sisal, ramie and flax are used to replace conventional glass fibers.…”
mentioning
confidence: 99%